Acute coronary syndromes in patients with diabetes mellitus: a difficult task for the cardiologist and cardiac surgeon - Kuklińska, Agnieszka; Hirnle, Tomasz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2008)
Diabetes mellitus (DM) represents one of the most important risk factors of coronary artery disease. Unfavourable prognosis has been found in patients with DM and concomitant acute coronary syndromes (ACS). We present guidelines for diagnosis and treatment of ACS according to the recent recommendations of the European Society of Cardiology. Special issues related to the DM and ACS are discussed. Indications, methods of surgical coronary artery revascularization and perioperative management of patients with DM are also covered in this article.